2018
DOI: 10.5194/amt-11-65-2018
|View full text |Cite
|
Sign up to set email alerts
|

Development, characterization and first deployment of an improved online reactive oxygen species analyzer

Abstract: Abstract. Inhalation of atmospheric particles is linked to human diseases. Reactive oxygen species (ROS) present in these atmospheric aerosols may play an important role. However, the ROS content in aerosols and their formation pathways are still largely unknown. Here, we have developed an online and offline ROS analyzer using a 2 ,7 -dichlorofluorescin (DCFH) based assay. The ROS analyzer was calibrated with H 2 O 2 and its sensitivity was characterized using a suite of model organic compounds. The instrument… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 44 publications
0
19
1
Order By: Relevance
“…Thus, despite the widespread dominance of biogenic SOA, especially during summer, SOA formed from anthropogenic precursors might still dominate the PB-ROS burden in the atmosphere. Previously we have shown that the degree of oxygenation and the OA loading do influence the PB-ROS content of aerosols in a specific source (biomass burning) (Zhou et al, 2018b).…”
Section: Source Contributions To Pb-rosmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, despite the widespread dominance of biogenic SOA, especially during summer, SOA formed from anthropogenic precursors might still dominate the PB-ROS burden in the atmosphere. Previously we have shown that the degree of oxygenation and the OA loading do influence the PB-ROS content of aerosols in a specific source (biomass burning) (Zhou et al, 2018b).…”
Section: Source Contributions To Pb-rosmentioning
confidence: 96%
“…For the secondary wood burning emissions, only the experiments conducted with one of the conventional single-stage combustion logwood stoves and aged in the PSI-MSC are presented here, as it is more representative for the genuine atmospheric ag-ing (with an OH exposure of (2.6-4.8) ×10 7 molec cm −3 h), compared to the emissions from the other burning devices that were aged in the potential aerosol mass (PAM) chamber (with an OH exposure of (1.1-2.0) ×10 8 molec cm −3 h). More details of the experimental method as well as the evolution of PB-ROS formation during the aging can be found in our previous publication (Zhou et al, 2018b).…”
Section: Measurement Campaignsmentioning
confidence: 99%
“…The association with NO 3 -, is much more surprising. Given that ammonium nitrate and ammonium sulphate do not exhibit any sensitivity towards both AA and DTT assays [28,74], this relation could be due to the redox organic pollutants (nitro-PAHs for instance) which can probably secondary be formed at the same time as NO 3 - [44].…”
Section: Contrasts Between Sitesmentioning
confidence: 98%
“…Most ROS analysis techniques mentioned above use offline filter-based methods, where aerosols are analyzed hours (h) or days after collection and therefore likely severely underestimate the true particle-bound, exogenous ROS concentrations because the reactive and short-lived components of ROS such as radicals or some peroxides decay before analysis Krapf et al, 2016;Zhou et al, 2018a;Bates et al, 2019). This makes it difficult to gauge their impact on human health, especially to identify which particle sources contribute to ROS and what atmospheric conditions affect ROS formation in a real-world urban environment.…”
Section: Introductionmentioning
confidence: 99%